Memento Mori: рассказы не для нервных : перевод с английского / сост. А. В. Березнев - Березнев А. В. (Старый свет : Паблисити, 1992)
Экземпляры: Ф. 11 (20200930) / Инвентарный номер: 45189 / Цена: 30.00 / Сис.шифр: 84(0) / Авт.знак: M 54 / ГРНТИ: 17.82 / ББК: 84(0)